PRODUCT ADVANTAGE ANALYSIS BASED ON MARKET UNDERSTANDING AT PT SAMATOR GAS KALIWUNGU KENDAL - Ageng Prasetyo; Nurkholik Nurkholik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze how the company need to understand about the customers expectation before the new product was launched to the market place, especially at the PT Samator Gas, Kaliwungu, Kendal. The capacity of the company to understand the market was called the market knowledge competence. Its concist of three major aspects such as customer knowledge competence, competitor knowledge competence and the interface between R&D with marketing department. The higher market knowledge competence has been estimated can creates the higher the product excellence in the market place. And as the result the product excellence may increase the marketing performance, these was inluded sales volume, sales growth and customers growth. The amount of the population on this research were 500 customers of the company. But the sample were 100 customers, which devided into two categories of monthly purchasing amount. The result of this research were the higher of customer knowledge competence, the higher of competitor knowledge competence and the higher of the relation R/D and marketing influenced the higher of product excellence. So the higher of product excellence influenced the higher of marketing performance.